Jesus in America: and other stories from the field - Gould, Claudia (Utah State University Press, 2009)
Drawing on ethnographic field work she conducted among Christians in her home state of North Carolina, Claudia Gould crafts stories that lay open the human heart and social complications of fundamentalist belief. These stories and the compelling characters who inhabit them draw us into the complex essence of religious experience among southern American Christians